A Study on the production system of MK Screens, Incorporated - Boyonas, Mark Ismael; Encinas, Catherine; Generelao, Lynn Mae. (Diliman, Quezon City College of Engineering, 2002)
aMK Screens is the leading manufacturer of Gabions and Mattresses. Gabions and Mattresses are rectangular frames which functions as soil erosion and landslips prevention. Sizes of these products come in standard sizes and may be changed according to customer specifications. This study will tackle three problems experienced by MK Screens in their existing production system. These are inefficient plant layout, forecasts are based on orders placed and "gut-feel" , and inefficient production planning. Information needed to examine these problems were gathered from interviews with the plant manager, observations on the plant site by the group and the review of historical data of the company. With these at hand, the group was able to come up with possible solutions to the problems. The inefficiencies in the lay-out can be eliminated by doing minor changes in the orientation of the machines. By doing so, an estimated decrease and elimination of 105 meters of unnecessary traveling distance was made. By eliminating the unnecessary travel by the forklift, potential savings on gasoline and manpower could be made. For the forecasting problem, the group found out that they just base their forecasted demand of raw materials on the orders placed an not playing any forecasting technique. Thus, the group came up with two possible methods and found out that of the two, the multiplicative seasonal method is best suitable to their system. This method yields the lowest Mean Average Deviation (MAD) which depicts the difference between the actual and the forecasted demand. The production planning system of the firm could be improved by implementing an aggregate based plan tabulating the production schedule as against the forecasted demand levels with the amount of over-time and subcontracted levels of production.
IE 151
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: MK Screens, Incorporated; Screens; Production engineering